PERAN KLUB BELAJAR DALAM MENINGKATKAN MINAT DAN PRESTASI AKADEMIK SISWA DI SMAN 4 DENPASAR - aulia, Nurul; Ta'rifin, Ahmad (Dahzain Nur, 2024)
This research aims to determine the role of study clubs in increasing students' interest and academic achievement at SMA N 4 Denpasar. The research method used is a qualitative method with a case study approach. Data was collected through interviews, observation and documentation. The research results show that study clubs have a significant role in increasing students' interest and academic achievement. Study clubs provide a fun learning atmosphere, facilitate students' learning needs, and provide intensive study guidance. This has an impact on increasing students' interest in learning and their academic achievements, especially in the subjects that are the focus of study clubs. Study clubs also help students develop independent learning skills and increase their self-confidence. The conclusion of this research is that study clubs have an important role in increasing students' interest and academic achievement at SMA N 4 Denpasar. These findings indicate that study clubs play a significant role as a platform that supports the development of students' potential, both in terms of interest and academic achievement